Synthesis, Urease Inhibition, Antioxidant, Antibacterial, and Molecular Docking Studies of 1, 3, 4-Oxadiazole Derivatives. (13th August 2012) - Hanif, Muhammad; Shoaib, Khurram; Saleem, Muhammad; Hasan Rama, Nasim; Zaib, Sumera; Iqbal, Jamshed
Abstract : A series of eighteen 1, 3, 4-oxadiazole derivatives have been synthesized by treating aromatic acid hydrazides with carbon disulfide in ethanolic potassium hydroxide yielding potassium salts of 1, 3, 4-oxadiazoles. Upon neutralization with 1 N hydrochloric acid yielded crude crystals of 1, 3, 4-oxadiazoles, which were purified by recrystallization in boiling methanol. The synthesized 1, 3, 4-oxadiazoles derivatives were evaluated in vitro for their urease inhibitory activities, most of the investigated compounds were potent inhibitors of Jack bean urease. The molecular docking studies were performed by docking them into the crystal structure of Jack bean urease to observe the mode of interaction of synthesized compounds. The synthesized compounds were also tested for antibacterial and antioxidant activities and some derivatives exhibited very promising results.